Study of three-dimensional spatial diffuse discharge in contact electrode structure applied to air purification - XU, Shuai; LIU, Wenzheng; QIN, Jiaying; SUN, Yiwei; JIANG, Xitao; QI, Qi (Plasma science & technology, 2024)
In this work, based on the role of pre-ionization of the non-uniform electric field and its effect of reducing the collisional ionization coefficient, a diffuse dielectric barrier discharge plasma is formed in the open space outside the electrode structure at a lower voltage by constructing a three-dimensional non-uniform spatial electric field using a contact electrode structure. The air purification study is also carried out. Firstly, a contact electrode structure is constructed using a three-dimensional wire electrode. The distribution characteristics of the spatial electric field formed by this electrode structure are analyzed, and the effects of the non-uniform electric field and the different angles of the vertical wire on the generation of three-dimensional spatial diffuse discharge are investigated. Secondly, the copper foam contact electrode structure is constructed using copper foam material, and the effects of different mesh sizes on the electric field distribution are analyzed. The results show that as the mesh size of the copper foam becomes larger, a strong electric field region exists not only on the surface of the insulating layer, but also on the surface of the vertical wires inside the copper foam, i.e., the strong electric field region shows a three-dimensional distribution. Besides, as the mesh size increases, the area of the vertical strong electric field also increases. However, the electric field strength on the surface of the insulating layer gradually decreases. Therefore, the appropriate mesh size can effectively increase the discharge area, which is conducive to improving the air purification efficiency. Finally, a highly permeable stacked electrode structure of multilayer wire-copper foam is designed. In combination with an ozone treatment catalyst, an air purification device is fabricated, and the air purification experiment is carried out.